Security Enhancement in Power System Using FACTS Devices and Atom Search Optimization Algorithm - Amarendra, A; Ravi Srinivas, L; Srinivasa Rao, R (EAI Endorsed Transactions on Energy Web, 2021)
In power systems, control, system operations are an important and difficult task by enhancing the power systems' security. An enhancement of the security system is done by the optimal location selection of the Flexible Alternating Current Transmission System (FACTS) devices, for instance, Unified Power Flow Controller (UPFC), Thyristor-Controlled Series Capacitor (TCSC), Interlink Power Flow Controller (IPFC), and Static VAR Compensator (SVC). Therefore, the Atom Search Algorithm (ASO) is utilized to compute the precise optimal placement of the FACTS device. FACTS devices must be in the correct location on the power system to improve system safety. The performances are evaluated by severity index, Line Overload Sensitivity Index (LOSI), voltage, voltage deviation ̧, power loss, fitness function, and the fuel cost with the IEEE 30, IEEE 118, and IEEE 300 bus system. To validate the proposed methodology, it is contrasted with the conventional techniques like Dragonfly Algorithm (DA), Whale Optimization Algorithm (WOA), Jaya, Flower Pollination Algorithm (FPA), Grey Wolf Algorithm (GWA), and the Jaya Flower Pollination (JA-FPA) systems.
Keywords: FACTS devices; optimization; security enhancement; stability; reliability; optimal power flow; constraints; location; atom search algorithm; and severity index